Design desejante: a dobra como espaço e(ntr)e - Borges, Maria Lucília (2008)
When sound came to be part of the design universe, it became necessary to investigate in what measure design has changed its nature and has escaped from its (visual) common place , so as to deterritorialise in virtual spaces such as the space of music. We start from the principle that music and design not only can be of same nature as they can occupy the same territory, since what defines them is potency, what renders them possible and passive of actualise as sound, image, image-movement, image-thought.... We do not exactly study the finished piece in the music of this or other composer, or even a particular design product, but that which precedes its actualisation: machinic potency. In order to do so, it was necessary to sketch out a cartography of the concept of design so as to demonstrate that design is potentially and conceptually inscribed in the music, since it carries in its own name the future potency (the projéctil). If design is projéctil, it bears a potency for projection. If we are here dealing with potencies, with the power to affect and being affected (as shown by Spinoza), and if all is flux and is in process (as stated by David Bohm), then this projection potency is a production potency, and if production is of the universe of machines, we can then state that everything is machines (as also stated by Gilles Deleuze and Félix Guattari), from the object to the subject, from the living being to the non-living, from the biosphere to the mechanosphere. What defines a machine (according to Humberto Maturana and Francisco Varela) is the relations it produces within or without, and not the elements that constitute it, or the function to which the machine is ascribed. These are the relationships that interest us here. The relationships that a machine (living or not) is capable of producing, the affects and the consequent sensations that it is capable of triggering, the power (potency) of affecting and being affected, production as process that exceeds all ideal categories and forms a cycle that refers to desire as immanent principle (as stated by Deleuze and Guattari). Desire, in the sense adopted here (according to Deleuze and Guattari), is not restricted to the human, as machines are not restricted to the universe of science/technology. The body is a machine, and as machines are bodies. Bodies and machines are living beings .Here, the alive is flux, the living is one that has a will for potency (as stated by Nietzsche), a power to affect and be affected, and its dynamic relationships. Living is everything that is conserved in the continuity of the flux. It is sensation. Machines for the production of consumption (industrial) are not included within this everything, but, instead, we include all desire producing machines, desiring machines, where the product is the very production of production and where production is process, desiring production. It is by sensation that machines live , a life that stretches beyond the machine s limits, crosses generations and is conserved within objects and subjects, potencies of sensation. Thus, from the concept of art as desiring machines we seek to find a elementary particle of the projectiles (music and design), unfolding the line of becoming that perpasses (and preexists as potency) the history of design or of music